Gejala Asimetris pada Lele Afrika Clarias gariepinus Tak Bersirip Pektoral Hasil Buidaya di Kolam - Farikhah Farikhah; Sukoso Sukoso; U Yanuhar; F Iranawati; M Zainuddin (Universitas Gadjah Mada, 2017)
The purpose of this study was to describe the asymmetric potential possessed by the pectoral fin organ Clarias gariepinus catfish originating from maintenance in aquaculture ponds. Individuals who do not grow a pair of pectoral fins are mated to a normal pectoral finned individual to obtain fish seed (F1). The study was conducted from January to April 2017 at the Reproductive Laboratory of Aquaculture Studies Program Department of Water Resources Management Faculty of Fisheries and Marine Science Universitas Brawijaya Malang. The observed variables are asymmetric score and Asymmetric Fluctuation Index (FA). The number of lefts and right pectoral fin radius, as well as abnormal F1 percentage, were analyzed. Long-weight relationship was analyzed by linear regression and PT/BB ratio. The conclusions using Mann Whitney-U Test (α = 0.01). The results showed that the population of F1 from the parent fish of the non-pectoral mortal differs very significantly with the controls on the asymmetry score variables (13.63±29.88), FA (1.25±2.05), the average number of pectoral left fins (8.95±3.22) - right fin (9.10±1.89), and the ratio of PT/BB (1.57±0.61) with a long-weighted relationship based on the equation y = 3.25x-2.04. Based on the results of this study it is concluded that the catfish Afrika Clarias gariepinus with perfect loss pectoral fin has the potency to generate asymmetrical characters to its generation and rising FA that is influenced by the hybridization or crosses.